Retrospondyloptosis of the Spine Secondary to Nonaccidental Trauma - T. S. Duffin; S. W. Thomas (Hindawi Limited, 2018)
Spinal fracture rates from NAT have been reported in <1-3% of spinal injury cases. We present a 13-month-old female who presented with signs of spinal cord injury and was found to have complete retrospondylolisthesis of T12 vertebra and multiple rib fractures in various stages of healing due to NAT. This case reports an extremely severe spinal injury due to NAT of which there are few in the literature and highlights the importance of suspicion of NAT when pediatric patients present with neurologic symptoms and spinal trauma without plausible mechanism of injury.